Pendekatan Dakwah Etis terhadap Kondisi Masyarakat Muslim Heterogen - Tajiri, Hajir (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
Daâ€™wah has two faces the existence of whichÂ depends to daâ€™i. When daâ€™wah is done by daâ€™i having minimum competency in knowledge and faith, the performance of daâ€™wah become fearing, in-productive, horrify and fearsome. On the contrary if daâ€™wah is done by daâ€™i havingÂ a lot of knowledge, strong faith, competency in using relevant method, so daâ€™wahâ€™s performanceÂ become good andÂ applicable to heterogeneous societies.